Hepatitis B virus testing by minipool nucleic acid testing: does it improve blood safety?. Issue 10 (23rd April 2013) - Stramer, Susan L.; Notari, Edward P.; Krysztof, David E.; Dodd, Roger Y.
Abstract : Background: Hepatitis B virus (HBV) DNA‐positive yield since nucleic acid testing (NAT) implementation (minipools of 16 [MP16]) was reported for the first year. We have updated those figures, evaluated the current value of all HBV tests, calculated the HBV residual risk before and after the introduction of MP‐NAT, and estimated residual risks with further improvements in HBV screening for US blood donations. Study Design and Methods: All donations were screened by US‐required serologic HBV tests and for HBV DNA by MP‐NAT (Novartis/Gen‐Probe). Further testing by individual‐donation polymerase chain reaction (ID‐PCR) confirmed various classes of MP‐NAT–reactive or –nonreactive donations. The hepatitis B surface antigen (HBsAg)‐yield method was used to calculate incidence and the incidence–window‐period model used to define residual risk. Results: Of approximately 12.8 million donations screened during 2009 to 2011, a total of 1368 HBV confirmed positives including 941 by MP‐NAT were observed (combined 4.32% positive predictive value) of which five were seronegative NAT‐yield donations (1:2.6 million) and 25 HBsAg‐yield (anti‐HBc–nonreactive) donations from which an incidence of 1.62/100, 000 person‐years (vs. 3.43 during 2006‐2008) and residual risk of 1:592, 000 to 1:754, 000 were calculated. With the addition of MP‐NAT, and resulting 8.8‐day window‐period reduction, residual risks decreased to 1:765, 000 to 1:1, 006, 000. Of the 1368 positives, 99.6% were detected by serology and 68.8% by MP‐NAT; ID‐PCR detected 427 more infected donors than MP‐NAT. Conclusions: HBV MP‐NAT and decreases in HBV incidence (likely vaccine‐related) in the United States have reduced residual risks to levels comparable to those of human immunodeficiency virus and hepatitis C virus and raise the question of the continued need for all three HBV markers for blood donation screening. Further reductions in residual risk will require the implementation of more sensitive HBV‐NAT methods including ID‐NAT.